2020
DOI: 10.1109/tap.2019.2927861
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Spectral Singularities in Non- Hermitian Cylindrical Structures

Abstract: Non-Hermitian systems characterized by suitable spatial distributions of gain and loss can exhibit "spectral singularities" in the form of zero-width resonances associated to realfrequency poles in the scattering operator. Here, we study this intriguing phenomenon in connection with cylindrical geometries, and explore possible applications to controlling and tailoring in unconventional ways the scattering response of sub-wavelength and wavelength-sized objects. Among the possible implications and applications,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Eqs. (72) and (73) are respectively known as the "reflection reciprocity" and "unitarity" relations. The latter implies that, for a real potential, R l/r and T are bounded functions.…”
Section: Spectral Singularities and Lasingmentioning
confidence: 99%
See 2 more Smart Citations
“…Eqs. (72) and (73) are respectively known as the "reflection reciprocity" and "unitarity" relations. The latter implies that, for a real potential, R l/r and T are bounded functions.…”
Section: Spectral Singularities and Lasingmentioning
confidence: 99%
“…This involves the computation of the M 22 (k) entry of the transfer matrix and finding the values of the physical parameters of the system for which M 22 (k) has a real and positive zero k ⋆ . This method has the advantage of being applicable to lasers with a variety of geometries and special properties [60,61,62,63,64,65,66,67,68,69,70,71,73,72].…”
Section: Spectral Singularities and Lasingmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-Hermitian optics concepts are particularly intriguing in ENZ media, where the effects of relatively low levels of loss and/ or gain can be dramatically enhanced (30)(31)(32). For instance, recent studies have demonstrated a variety of interesting effects including tunneling (33), waveguiding (34), coherent perfect absorption (35), immunity to impurities (36), exceptional points and spectral singularities (37,38), and nonlinear and nonreciprocal effects (17).…”
mentioning
confidence: 99%
“…dealing with cylindrical non-Hermitian configurations (38,52), it has been shown that unconditional stability could be, in principle, attained by suitably tailoring the dispersion properties of the material constituents. In SI Appendix, Fig.…”
mentioning
confidence: 99%